Finite element analysis of the influence of cohesive law parameters on the multiple delamination behaviors of composites under compression. (1st November 2015) - Liu, P.F.; Gu, Z.P.; Peng, X.Q.; Zheng, J.Y.
Abstract: Interaction between the delamination and postbuckling of composite laminates under compressive load is an important issue. The evolving profile of nonlinear fracture process zone due to delamination crack propagation is largely affected by the geometrically nonlinear behavior of composites. Until now there is no unified cohesive zone model (CZM, or called cohesive law) that can represent all true fracture process zones during the delamination of composites under various loads and environments. The purpose of this paper is to study the influence of cohesive law parameters on the postbuckling and delamination behaviors of composites under compression by 3D finite element analysis (FEA). An improved Xu and Needleman's CZM and a bilinear CZM are used to study multiple delamination growth comparatively. Taking the composite flat laminates with initial through-the-width multiple delaminations as example, the effects of cohesive shape, cohesive strength and cohesive element thickness on the delamination behavior are studied. The proposed model is validated by using experimental data and its robustness and computational efficiency are highlighted by comparing with different CZMs. It is found that the fracture process zone is largely affected by the geometrically nonlinear deformation at the unstable delamination stage between the initial buckling and global buckling.